GPT Chat Integration in Project Based Learning in Learning: A Systematic Literature Review - Iwan Purnama; Firman Edi; Syahrul; Risnawati Agustin; Nuridin Widya Pranoto (Postgraduate, University of Mataram, 2023)
The evolution of technology in education has opened new doors for innovative teaching methods. One such breakthrough tool is ChatGPT, a learning model developed by Open AI. Open AI has huge potential, not only to increase efficiency but also to improve pedagogy for more engaging learning experiences. The purpose of this research is to test the integration of GPT Chat in Project Based-Learning in Learning. This research uses a systematic literature review method using Preferred Reporting Items for Systematic Reviews (PRISMA). The results of this research explain that in the Industrial Revolution Era 4.0, educational institutions must prepare new literacy and orientation in the field of education, the new literacy itself is in the form of data, technology, and human resource literacy. Project-based learning is a learning model that emphasizes student activity in solving various problems through a series of activities starting with gathering information, planning a project, and producing a particular product packaged in the form of project work. The stages of project-based learning are Determining basic questions, developing a project plan, Developing a schedule, Monitoring, Test results, and Evaluation of experience. ChatGPT is a research tool or â€œthought partnerâ€, and is said to be useful for a variety of teaching purposes. The application of the PjBL model has the potential to improve student learning outcomes and motivation in Indonesia. Therefore, the integration of GPT chat with Project Based-learning in learning needs to receive further attention so that it can make a more significant contribution to improving the quality of learning and student motivation in Indonesia.